Rock mechanics in underground construction [compact disc] : ISRM International Symposium 2006 : 4th Asian Rock Mechanics Symposium, 8 - 10 November 2006, Singapore - Leung, C. F.; Zhou, Yingxin (Hackensack, NJ : World Scientific Publishing Company, 2006)
08